Comparative analysis of the influence of clinical factors including BMI on adalimumab and infliximab trough levels. Issue 3 (March 2016) - Bond, Ashley; Asher, Rebecca; Jackson, Richard; Sager, Khalid; Martin, Kate; Kneebone, Andrew; Philips, Suzannah; Taylor, William; Subramanian, Sreedhar
Abstract : Introduction: Optimal trough levels of the anti-tumour necrosis factor agents, infliximab and adalimumab, are correlated with clinical remission. Obesity adversely affects response to infliximab and adalimumab, but the influence of BMI on trough levels has not been adequately investigated. We investigated the relationship between clinical variables, including BMI, and trough levels of infliximab and adalimumab. Methods: This prospective cross-sectional study included patients treated with infliximab and adalimumab on maintenance therapy, with concurrent measurements of trough levels and BMI. The associations between categorical trough levels and clinical variables, including BMI, were estimated. Results: Of the 122 patients included in the study, 80 (66%) were on infliximab and 42 (34%) were on adalimumab. Eighty-three per cent had Crohn's disease and the remainder had ulcerative colitis. None of the clinical variables, including smoking, BMI, concurrent immunosuppression, duration of disease and treatment, were associated with categorical trough levels of infliximab or adalimumab. The effect of BMI did not differ between the two anti-tumour necrosis factor agents, although there was a trend towards a lower trough level in adalimumab-treated patients with a BMI greater than 30 ( P =0.09). In infliximab-treated patients, antibodies to infliximab ( P <0.001) and a C-reactive protein level of at least 5 mg/dl were associated with trough levels less than 3 µg/ml ( P =0.008). Conclusion: BMI does not differentially influence trough levels of adalimumab and infliximab, although a trend towards a lower trough level was observed in adalimumab-treated patients with a BMI greater than 30. Raised C-reactive protein levels and antibodies to infliximab were associated with subtherapeutic levels of infliximab.